A STORYTELLING IN LANGUAGE TEACHING : STORYTELLING IN LANGUAGE TEACHING - Hasibuan, kalayo; klaudia, sindi; Yuliani Puspita, Suci; Dwi Putri , Shalsabila; Ulya, Zainatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Storytelling is an effective strategy in language teaching that can improve students’ language competence and classroom participation. This method provides meaningful learning experiences by integrating listening, speaking, reading, and writing skills into one activity. Through storytelling, students are able to enrich their vocabulary, improve pronunciation, understand grammar usage, and develop communication skills more confidently. In addition, storytelling encourages students’ creativity, imagination, and critical thinking during the learning process. The use of stories from everyday life, local culture, folklore, or personal experiences can make language learning more engaging and understandable for learners. Furthermore, storytelling creates an interactive and student-centered classroom atmosphere that motivates students to participate actively in learning activities. Therefore, storytelling is considered an important and innovative approach in language teaching because it not only enhances students’ language proficiency but also increases motivation, confidence, and active involvement in the classroom.